Tracking motor activity in Virtual Reality to reveal cognitive functioning: A preliminary study - Ribeiro, Nicolas; Vigier, Toinon; Prié, Yannick (International Journal of Virtual Reality, 2021)
A challenge for cognitive research is the better understanding of how motor activity influences and is influenced by other cognitive domains. We developed a preliminary study to investigate whether tracking motor functioning in virtual reality provides useful insight on cognitive functioning. We chose the flankers task as an assessment measure and built a VR environment into which seven participants completed more than 1250 trials. In addition to classical results of the flankers task showing that incongruent stimuli induce slower responses than others., we also identified how individuals are able to correct their initially incorrect motor response. This indicator may shed new light into the functioning of cognitive control in the future. We discuss the potential offered by virtual reality technology for cognitive assessment through embodied considerations of cognition.